Fish, State Park of Jalapão, State of Tocantins, Brazil - Aloísio, Gustavo Ribeiro (2005)
A Fast Environmental Diagnosis of fish was carried out in the State Park of Jalapão to support the implementation of its Management Plan. The survey of the fish community revealed the occurrence of 44 species distributed in three main rivers: Soninho, Novo and Sono and their tributaries